Infusion Rate Escalation Study of Rituximab in Patients with CD20+ B-Cell Lymphomas: A Single Institution Analysis in Japan. (3rd April 2013) - Yokoyama, Masahiro; Terui, Yasuhito; Takeuchi, Kengo; Nara, Eriko; Nakano, Kenji; Ueda, Kyoko; Nishimura, Noriko; Mishima, Yuko; Sakajiri, Sakura; Tsuyama, Naoko; Ozawa, Keiya; Hatake, Kiyohiko
Abstract : Background . To determine the maximum tolerable infusion rate of rituximab, and investigate the safety and feasibility of rapid infusion of rituximab for patients with CD20 positive B-cell lymphomas (CD20+NHL). Patients and Methods . 18 patients with CD20+NHL were registered. This study had six cohorts of administration rate of rituximab. The median age was 56 years (range, 38–79), and five of 18 patients were male. Two patients (11%) with diffuse large B-cell lymphoma were receiving R-CHOP therapy, two (11%) with indolent lymphoma were receiving R-CVP therapy, and 14 (78%) with indolent lymphoma were receiving rituximab as maintenance therapy. Results . A total of 88 cycles of rituximab was administered. Rapid infusion of rituximab was well tolerated, with only one grade 3 leukocytepenia and one grade 4 neutropenia. Four patients (22%) developed grade 1 infusion-related toxicities at the first administration of rituximab. No patient with severe drug-related events was observed. Conclusions . We determined that the maximum tolerable infusion rate of rituximab is 300 mL/h (under 700 mg/h), and confirmed that administration of over 60 minutes is safe and feasible. We recommend rapid administration of rituximab for practice setting in patients with CD20+NHL being treated with rituximab or rituximab-containing chemotherapy. (Clinical trial no. JFCR2009-1027).